Comparison of in vitro toxicity of silver ions and silver nanoparticles on human hepatoma cells. Issue 6 (28th November 2014) - Vrček, Ivana Vinković; Žuntar, Irena; Petlevski, Roberta; Pavičić, Ivan; Dutour Sikirić, Maja; Ćurlin, Marija; Goessler, Walter
ABSTRACT: Scientific information on the potential harmful effects of silver nanoparticles (AgNPs) on human health severely lags behind their exponentially growing applications in consumer products. In assessing the toxic risk of AgNP usage, liver, as a detoxifying organ, is particularly important. The aim of this study was to explore the toxicity mechanisms of nano and ionic forms of silver on human hepatoblastoma (HepG2) cells. The results showed that silver ions and citrate‐coated AgNPs reduced cell viability in a dose‐dependent manner. The IC50 values of silver ions and citrate‐coated AgNPs were 0.5 and 50 mg L −1, respectively. The LDH leakage and inhibition of albumin synthesis, along with decreased ALT activity, indicated that treatment with either AgNP or Ag ions resulted in membrane damage and reduced the cell function of human liver cells. Evaluation of oxidative stress markers demonstrating depletion of GSH, increased ROS production, and increased SOD activity, indicated that oxidative stress might contribute to the toxicity effects of nano and ionic forms of silver. The observed toxic effect of AgNP on HepG2 cells was substantially weaker than that caused by ionic silver, while the uptake of nano and ionic forms of silver by HepG2 cells was nearly the same. © 2014 Wiley Periodicals, Inc. Environ Toxicol 31: 679–692, 2016.